Reoperative Thyroid Surgery in Hospital Universiti Sains Malaysia - Tun, Myint (Penerbit Universiti Sains Malaysia, 2003)
From 1996 to 2001, 393 thyroidectomies were performed and 25 (6.4%) patients underwent reoperative thyroid surgery at Hospital Universiti Sains Malaysia. All reoperated patients had undergone one prior thyroid operation. All were females with an average age of 39.1 years (18–61 years). The most frequent indication for reoperation was cancer in resected specimen of an originally misdiagnosed carcinoma treated by partial thyroid resection. Final histological diagnosis of 25 reoperations showed thyroid carcinoma in 22 (88%) cases and multinodular goiter in 3 cases. The overall interval between the initial and the reoperative procedures ranged from 3 weeks to 15 years. There was no post-operative mortality after reoperation. Post-operative complications were discovered in 5 patients, as 3 (12%) of whom had transient hypocalcaemia, one (4%) had wound breakdown and one (4%) had permanent recurrent laryngeal nerve palsy. Reoperative thyroid surgery is an uncommon operation with high complication rate.